Designing Multimedia Through Interactive CD in Understanding Three Tenses - Belinda Analido (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2015)
Spoon-feeding technique is still used by some lecturers in teaching Grammar. In spite of the role of lecturer as the provider of knowledge, the students need to actively participate either inside or outside of the classroom. Transferring valuable knowledge becomes simpler by providing the product of multimedia consisting texts, graphics, photographs, sound, video, animation. The students have many opportunities to learn tenses from the product of multimedia independently without lecturer presence. Thus, this research is aimed at developing multimedia through interactive CD based macromedia flash in learning three tenses particularly Simple Future Tense, Future Continuous Tense, and Past Continuous Tense.  This study is Research and Development. The subject of this research is the first semester students of English Education Department who take Grammar I. The steps of development are defining, developing, and evaluating multimedia. The findings of the research show that the software quality of multimedia is fairgood based on the judgement of subject expert, media expert, and the first semester students who take Grammar I.This product(Interactive Compact Disk) meets the teaching objectives of Grammar I subject.